Electrophysiological evidence of subclinical trigeminal dysfunction in patients with COVID-19 and smell impairment: A pilot study - Cosentino, Giuseppe; Maiorano, Eugenia; Todisco, Massimiliano; Prunetti, Paolo; Antoniazzi, Elisa; Tammam, Giulia; Quartesan, Ilaria; Lettieri, Sara; De Icco, Roberto; Corsico, Angelo Guido; Benazzo, Marco; Pisani, Antonio; et al. (Frontiers in Neurology, 2022)
Background Smell and taste disturbances are among the most frequent neurological symptoms in patients with COVID-19. A concomitant impairment of the trigeminal nerve has been suggested in subjects with olfactory dysfunction, although it has not been confirmed with objective measurement techniques. In this study, we explored the trigeminal function and its correlations with clinical features in COVID-19 patients with impaired smell perception using electrophysiological testing. Methods We enrolled 16 consecutive patients with mild COVID-19 and smell impairment and 14 healthy controls (HCs). Olfactory and gustatory symptoms were assessed with self-reported questionnaires. Electrophysiological evaluation of the masseter inhibitory reflex (MIR) and blink reflex (BR) was carried out to test the trigeminal function and its connections within the brainstem. Results Masseter inhibitory reflex (MIR) analysis revealed higher latency of ipsilateral and contralateral early silent period in patients when compared with HCs. No significant differences between groups were detected as regards the duration of the early and late silent period. However, several patients showed a prolonged duration of the early silent period. BR evaluation disclosed only an increased amplitude of early components in patients. Conclusions Patients with COVID-19 and smell impairment show a subclinical trigeminal nerve impairment. Trigeminal alterations mainly involve the oligosynaptic pathway, as a result of either direct viral damage or secondary neuroinflammation of the peripheral trigeminal fibers, whereas the polysynaptic ponto-medullary circuits seem to be spared. The prolonged duration of the early silent period and the increased amplitude of early BR response might reflect a compensatory upregulation of the trigeminal function as a consequence of the olfactory dysfunction.